Computed Tomography Prevalence of Cervicothoracic Endplate Junction Alterations in Dogs - Carles Planas Padrós; Anna R. Tellegen; Henk van den Broek; Stefanie Veraa (Animals)
Spinal degenerative changes can predispose back pain and neurological deficits in dogs. In humans and veterinary patients, the endplate junction has been proposed as an alternative site of failure in addition to damage of the annulus fibrosus, leading to intervertebral disc herniation. Some alterations lead to contour abnormalities with or without regional mineralizations and can be classified as Endplate Junction Failure (EPJF), osteochondrosis (with or without fragmentation), or spondylarthritis. The objective of this retrospective study was to describe the prevalence of endplate junction alterations (EPJA) on CT in dogs at the cervicothoracic junction and classify alterations based on recent presumed EPJF grading. Computed tomographic scans of 315 dogs that included the cervicothoracic (C6–T2) spine for a variety of reasons obtained between January 2020 and December 2022 were assessed for the presence of alterations, location and type. Other spinal abnormalities were also described. A total of 945 intervertebral disc spaces were evaluated, and EPJA were found in 11 intervertebral disc spaces (1.16%). C6–C7 and C7–T1 intervertebral disc spaces were equally affected (five cases each), with only one case affecting T1–T2. In conclusion, cervicothoracic endplate alterations were anecdotically observed on CT in a population of dogs.